A Case With Bilateral Sacroiliitis and Polyneuropathy Development Due to Isotretinoin Use - Tuncay ÇAKIR,; Volkan SUBAŞI,; Adem BİLGİLİ,; Ümit Seçil DEMİRDAL,; Rahime Nur ÜLKER, (Archives of Rheumatology, 2014)
Isotretinoin is a vitamin A derivative used in acne treatment when standard treatment including systemic antibiotics fails. Isotretinoin exerts its effects via retinoic acid receptors. However, it often causes mucocutaneous, musculoskeletal, neurological, and ocular adverse effects. Most common musculoskeletal adverse effects include arthralgia and miyalgia. Rarely, seronegative sacroiliitis can be seen. Neurological adverse effects are generally related to central nervous system. In patients using isotretinoin, sensorial fibers are involved earlier than motor fibers in peripheral nervous system. This involvement is more prominent in sensorial nerves and myelin fibers at distal. In this article, we report a 25-year-old male case who developed demyelinating polyneuropathy and sacroiliitis after six-months of isotretinoin use.